DYRK1A in the physiology and pathology of the neuron-astrocyte axis - Cisternas, Pablo; Kim, Jiyoon; Ashfeld, Brandon; Zartman, Jeremiah (Frontiers in Neuroscience, 2025)
Dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) is a dosage-sensitive kinase with critical roles in the neuron-astrocyte axis. During brain development, DYRK1A ensures the proper number of differentiated neurons and astrocytes. In neurons, this DYRK1A regulates neuronal morphogenesis and synaptic transmission. However, its functions in astrocytes are not yet well defined, with limited evidence indicating roles in astrocyte reactivity and excitotoxicity. Due to trisomy 21, DYRK1A is overexpressed in individuals with Down syndrome (DS). This imbalance directly contributes to neuronal death and likely astrocyte pathology, accelerating the onset of Alzheimer’s disease (AD) in this population. Notably, DYRK1A overexpression also correlates with neurodegeneration and AD progression in elderly euploid adults. This correlation positions DYRK1A as a potential bridge between DS and AD, mechanistically connecting gene overdosage and neuropathology in both conditions. However, research on DYRK1A pathophysiology has primarily centered on neurons, leaving astrocytes largely understudied. Considering the vital neuroprotective functions of astrocytes, broadening DYRK1A research to encompass these cells presents an opportunity to uncover novel mechanisms contributing to the neurodegenerative process in AD. In this review, we highlight the physiology and pathology of DYRK1A in the neuron–astrocyte axis, analyzing its roles in neurons and positing hypothetical functions in astrocytes, with particular emphasis on the contribution of DYRK1A’s cell-specific overexpression to neurodegeneration and AD progression.